EFEITOS DO CONTROLE NAS INTENÇÕES COMPORTAMENTAIS DOS CONSUMIDORES INSATISFEITOS - Renaud Lunardo; Natália Araujo Pacheco; Cristiane Pizzutti dos Santos (RAE: Revista de Administração de Empresas, 2012)
Control has been cited as an essential element for developing satisfactory interpersonal relationships, positively related to satisfaction and to emotional and behavioral responses in consumer behavior. This work investigates the impact of behavioral, cognitive and decisional controls, represented by co-production, information and refund choice, respectively, on repurchase and positive word of mouth intentions after unsatisfactory purchases. The results from two experimental studies indicate that co-production and refund choice lead to higher repurchase and positive word-of-mouth intentions after dissatisfaction episodes, while information do not affect behavioral intentions but moderates the effect of co-production on behavioral intentions.